Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Microscopic structure and energy transfer of vacancy-related defect pairs with Erbium in wide-gap semiconductors - Konopka, A.; Greulich-Weber, S.; Dierolf, V.; Jiang, H.X.; Gerstmann, Uwe; Rauls, E.; Sanna, S.; Schmidt, Wolf Gero (Optical Materials)

Methane adsorption on graphene from first principles including dispersion interaction - Thierfelder, C.; Witte, M.; Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Driving forces for the adsorption of cyclopentene on InP(001) - Favero, P.P.; Ferraz, A.C.; Schmidt, Wolf Gero; Miotto, R. (Surface Science)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Tight‐binding model for the electronic and optical properties of nitride‐based quantum dots - Schulz, S.; Mourad, D.; Schumacher, Stefan; Czycholl, G. (physica status solidi (b))
Abstract Two slightly different, efficient tight‐binding (TB) models for the description of the electronic properties of nitride‐based semiconductor quantum dots (QDs) have been developed and applied to the calculation of the electronic one‐particle spectrum of these structures. Using these one‐particle QD‐states, dipole and Coulomb matrix elements can be calculated, from which the optical properties of these systems can be obtained. These TB calculations have been performed for nitride‐based QDs with a cubic zincblende structure and those with a wurtzite crystal structure. In this paper, we discuss the general methodology used and the results obtained for the electronic one‐particle states and energies, for the dipole and Coulomb matrix elements, and for the excitonic optical emission and absorption spectra.

Optical Excitations in Star-Shaped Fluorene Molecules - Montgomery, Neil A.; Denis, Jean-Christophe; Schumacher, Stefan; Ruseckas, Arvydas; Skabara, Peter J.; Kanibolotsky, Alexander; Paterson, Martin J.; Galbraith, Ian; Turnbull, Graham A.; Samuel, Ifor D. W. (The Journal of Physical Chemistry A)

Kontextorientiertes Lernen in der chemiedidaktischen Forschung - Fechner, Sabine; Bremkes, T.; Harbach, Andrea; Kölbach, Eva; Lindner, Martin; Nentwig, Peter; Parchmann, Ilka; Ralle, Bernd; Sumfleth, Elke; van Vorst, Helena (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Phonon-assisted decoherence and tunneling in quantum dot molecules - Grodecka-Grad, Anna; Förstner, Jens (physica status solidi (c))
We study the influence of the phonon environment on the electron dynamics in a doped quantum dot molecule. A non-perturbative quantumkinetic theory based on correlation expansion is used in order to describe both diagonal and off-diagonal electron-phonon couplings representing real and virtual processes with relevant acoustic phonons. We show that the relaxation is dominated by phononassisted electron tunneling between constituent quantum dots and occurs on a picosecond time scale. The dependence of the time evolution of the quantum dot occupation probabilities on the energy mismatch between the quantum dots is studied in detail.
Keywords: tet_topic_qd

Intensity-dependent ultrafast dynamics of injection currents in unbiased GaAs quantum wells - Pochwała, Michał; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (physica status solidi (RRL) - Rapid Research Letters)
The intensity dependence of optically-induced injection currents in unbiased GaAs semiconductor quantum wells grown in [110] direction is investigated theoretically for a number of well widths. Our microscopic analysis is based on a 14 x 14 band k . p method in combination with the multisubband semiconductor Bloch equations. An oscillatory dependence of the injection current transients as function of intensity and time is predicted and explained. It is demonstrated that optical excitations involving different subbands and Rabi flopping are responsible for this complex dynamics.
Keywords: tet_topic_qw

Oscillatory excitation energy dependence of injection currents in GaAs/AlGaAs quantum wells - Thanh Duc, Huynh; Förstner, Jens; Meier, Torsten; Priyadarshi, Shekhar; Racu, Ana Maria; Pierz, Klaus; Siegner, Uwe; Bieler, Mark (physica status solidi (c))
The injection of photocurrents by femtosecond laser pulses in (110)-orientedGaAs/AlGaAs quantum wells is investigated theoretically and experimentally. The roomtemperature measurements show an oscillatory dependence of the injection current amplitude and direction on the excitation photon energy. Microscopic calculations using the semiconductor Bloch equations that are set up on the basis of k.p band structure calculations provide a detailed understanding of the experimental findings.
Keywords: tet_topic_qw

Numerical investigation of the coupling between microdisk modes and quantum dots - Declair, S.; Meier, Torsten; Förstner, Jens (physica status solidi (c))
We numerically investigate the coupling between circular resonators and study strong light‐matter coupling of single as well as multiple circular resonators to quantum‐mechanical resonators in two dimensional model simulations. For all cases, the computed resonances of the coupled system as function of the detuning show anti‐crossings. The obtained mode splittings of coupled optical resonators are strongly depending on distance and cluster in almost degenerate eigenstates for large distances, as is known from coupled resonator optical waveguides. Vacuum Rabi splitting is observed for a quantum dot strongly coupled to eigenmodes of single perfectly cylindrical resonators.
Keywords: tet_topic_phc; tet_topic_microdisk

Numerical analysis of coupled photonic crystal cavities - Declair, S.; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
We numerically investigate the interaction dynamics of coupled cavities in planar photonic crystal slabs in different configurations. The single cavity is optimized for a long lifetime of the fundamental mode, reaching a Q-factor of ≈43, 000 using the method of gentle confinement. For pairs of cavities we consider several configurations and present a setup with strongest coupling observable as a line splitting of about 30 nm. Based on this configuration, setups with three cavities are investigated.
Keywords: tet_topic_phc